Functional Tuning of CARs Reveals Signaling Threshold above Which CD8+ CTL Antitumor Potency Is Attenuated due to Cell Fas-FasL-Dependent AICD - Künkele, Annette; Johnson, Adam J; Rolczynski, Lisa S; Chang, Cindy A; Hoglund, Virginia; Kelly-Spratt, Karen S; Jensen, Michael C (Cancer immunology research, 2015)
Chimeric antigen receptor (CAR) development is biased toward selecting constructs that elicit the highest magnitude of T-cell functional outputs. Here, we show that components of CAR extracellular spacer and cytoplasmic signaling domain modulate, in a cooperative manner, the magnitude of CD8(+)CTL activation for tumor-cell cytolysis and cytokine secretion. Unexpectedly, CAR constructs that generate the highest in vitro activity, either by extracellular spacer length tuning or by the addition of cytoplasmic signaling modules, exhibit attenuated antitumor potency in vivo, whereas CARs tuned for moderate signaling outputs mediate tumor eradication. Recursive CAR triggering renders CTLs expressing hyperactive CARs highly susceptible to activation-induced cell death (AICD) as a result of augmented FasL expression. CAR tuning using combinations of extracellular spacers and cytoplasmic signaling modules, which limit AICD of CD8(+)CTLs, may be a critical parameter for achieving clinical activity against solid tumors.